Example of the Application of the Use of the Case Points Method - Wolski, Michał; Pilski, Marek (Studia Informatica. System and information technology, 2019)
This text is the second one of the series of articles concerning projects estimation using the function points method. In the first part entitled: .Theoretical Aspects of Projects Estimation Using the Use Case Points Method" theoretical aspects of the function points method have been presented. Here, an example along with mathematical calculations will be discussed. Whilst in the part three entitled: "Project Estimation Using the Use Case Points Method When Using Enterprise Architect", a practical application of the function points method in Enterprise Architect have been presented.